Response to "comment on 'Enhanced biosorptive remediation of hexavalent chromium using chemotailored biomass of a novel soil isolate Bacillus aryabhattai ITBHU02: Process variables optimization through artificial neural network linked genetic algorithm'" - Verma D.K.; Hasan S.H.; Singh D.K.; Singh S.; Singh Y. (My University, 2025)
[No abstract available]